Emerging Mosquito-borne Diseases and the Potential of Integrated Strategies - A situation analysis of the latest Zika outbreak in Rio de Janeiro 2015/2016 - Juliane Bönecke (2019)
Introduction Factors such as climate, environment, along with a setting’s infra-structural, socio-economic and political characteristics are known to influence the spread of mosquitoborne diseases. In 2015 and 2016, Brazil became an increasingly affected country with epidemiological hot spots in the populous south-eastern regions including the municipality of Rio de Janeiro. In order to improve vector control and outbreak response in tropical metropolises it is important to better understand the complex ecology of urban mosquito-borne diseases and their primary vector Aedes aegypti as parts of a human-urban transmission cycle. Methods An information-rich case study was conducted following a mixed-methods approach to investigate the Zika outbreak scenario in Rio de Janeiro 2015/2016 from multiple perspectives. The findings derived serve as a basis for a comprehensive situation and hazard analysis considering the latest mosquito-borne disease outbreaks in Rio de Janeiro that follows two established tools applied to the field of emerging infectious diseases – a multiperspective “Situation and Influencing Factors Analysis” and the “Hazard Analysis and Critical Control Points” technique. Results Looking at the case of Rio de Janeiro 2015/2016, environmental and climatic conditions could be identified as a fundamental basis for the spread of urban mosquito-borne diseases, with a particular focus on the initial and final epidemiological trend. Demographic, socio-economic, and infrastructural vulnerabilities may furthermore influence the extent of an outbreak that could be identified in the centered areas of the city. Based on these findings, integrated vector control and outbreak management strategies are needed that take the peculiarities of an affected setting into account following the achievements, challenges and lessons learned during the Zika outbreak scenario in Rio de Janeiro 2015/2016. Conclusion This thesis explores the potentials of integrated knowledge, methodology and experiences as one solution approach to be able to point out not only risk factors and vulnerabilities, but also resources and solution approaches to develop an adequate response to MBD outbreaks within tropical metropolises like Rio de Janeiro.